Simplified filtered Smith predictor for MIMO processes with multiple time delays. (November 2016) - Santos, Tito L.M.; Torrico, Bismark C.; Normey-Rico, Julio E.
Abstract: This paper proposes a simplified tuning strategy for the multivariable filtered Smith predictor. It is shown that offset-free control can be achieved with step references and disturbances regardless of the poles of the primary controller, i.e., integral action is not explicitly required. This strategy reduces the number of design parameters and simplifies tuning procedure because the implicit integrative poles are not considered for design purposes. The simplified approach can be used to design continuous-time or discrete-time controllers. Three case studies are used to illustrate the advantages of the proposed strategy if compared with the standard approach, which is based on the explicit integrative action. Abstract : Highlights: A simplified tuning strategy for the MIMO filtered Smith predictor is proposed. Constant set-point tracking is achieved without an explicit integral action. The proposed approach can be used to control open-loop unstable systems.